Three-term back propagation neural network for moisture prediction - Said Jadid Abdulkadir, 1986-; Siti Mariyam Shamsuddin, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (2012)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2012